PENGARUH KADAR PROPILEN GLIKOL, TWEEN 80 DAN BESAR ARUS IONTOFORESIS TERHADAP TRANSPOR TRANSDERMAL PROMETAZIN HCL SECARA IN VITRO - , Dwi Nurahmanto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Promethazine HCl undergoes extensive hepatic first-pass metabolism following oral administration resulted in a low bioavailability at around 25%. Oral absorption is often interrupted by nausea and vomiting, so the bioavalability is low and morning sickness is not treated verry well. The purposes of this study were to evaluate the : 1) influence of propylene glycol, Tween 80 concentrations as enhancer and iontophoretic current density on the transport of promehtazine HCl, 2) to determine theoretical composition of optimum condition transdermal delivery system of promethazine HCl in transdermal preparation in vitro. Eight condition were prepared according to 23 factorial design employing propylene glycol, Tween 80 and iontophoretic current density. Ehancement effect on transport of prometazin HCl was investigated across hairless rat skin as membrane. The study was carried out by using vertical diffusion cell (franz cell like). Transport of promehtazine HCl across membrane was determined spectrophotometrically at ëmax 251 nm. Data were analysed based on WinSAAM compartement modeling to determine transport kinetics and the effects of enhancers. Optimization was conducted by factorial design using Design Expert ® 7.1.4 software. Increasing propylene glycol concentration and the current of iontophoretic significantly increased the Cp max, AUC and also the potential of the drug to difuse (AD). Increasing Tween 80 concentration significantly decrease the Cp max, AUC and also AD. Interactions of propylene glycol and iontophoretic current density significantly increase Cp max, AUC and AD. Interaction of Tween 80 and propylene glycol and also interaction of Tween 80 and iontophoretic current density significantly decrease Cp max, AUC and AD. Based on values of Cp max, AUC and AD optimum composition of the condition containing propylene glycol, Tween 80 and iontophoretic current density which have the percentage and current density of 20%, 1% and 0,5 mA/cm2, respectively. Theoritically, this composition has Cp max, AUC and AD value of 775,519 ng/L, 121 ,073 ìg and 165,686 ìg.